Effects of thirty and sixty minutes of moderate-intensity aerobic exercise on postprandial lipemia and inflammation in overweight men: a randomized cross-over study - Emerson, Sam R.; Kurti, Stephanie P.; Snyder, Brian S.; Sitaraman, Karthikeyan; Haub, Mark D.; Rosenkranz, Sara K. (My University, 2017)
Background: The transient rise in blood lipids following a high-fat meal (HFM), known as postprandial lipemia, is linked to systemic inflammation and cardiovascular disease, but can be blunted by exercise. However, minimal research has investigated the effects of realistic exercise bouts on postprandial lipemia and inflammation in at-risk individuals. The purpose of this study was to assess the effects of moderate-intensity aerobic exercise lasting 30 or 60 min performed the evening before a HFM, on postprandial lipemia and inflammation in overweight, insufficiently active men. Methods: In this randomized-crossover study, twelve participants remained sedentary (CON), or performed a brisk walk on a treadmill at 60 % VO2peak for either 30 min (EX-30) or 60 min (EX-60), after which they consumed a small snack (270 kcal) to partially replace exercise energy expenditure. Following a 12-h overnight fast, participants consumed a standard HFM (1 g fat/kg; 1 g CHO/kg; 1117.8 +/- 117.0 kcal). Blood draws were performed at baseline (pre-HFM) and 1, 2, 4, 6, and 8 h post-HFM to assess glucose, insulin, lipids, and systemic inflammation. Results: There were no significant differences (p > 0.05) in fasting triglycerides between EX-60 (118.7 +/- 68.3 mg/dL), CON (134.8 +/- 66.2 mg/dL) or EX-30 (135.5 +/- 85.4 mg/dL). There were no differences in peak, time-to-peak, total or incremental area-under-the-curve between trials for triglyceride response (p > 0.05). There was no significant main effect of time (p > 0.05) in IL-1ra, IL-4, IL-5, IL-6, IL-10 or TNF-alpha from baseline to 8 h post-HFM in any trial. Conclusions: In summary, we found that in overweight, insufficiently active men, neither 30 nor 60 min of moderate-intensity exercise performed 12 h prior to a HFM attenuated postprandial lipemia or inflammation, which could potentially be explained by the partial caloric replacement of exercise energy expenditure.
Citation: Emerson, S. R., Kurti, S. P., Snyder, B. S., Sitaraman, K., Haub, M. D., & Rosenkranz, S. K. (2016). Effects of thirty and sixty minutes of moderate-intensity aerobic exercise on postprandial lipemia and inflammation in overweight men: a randomized cross-over study. Journal of the International Society of Sports Nutrition, 13, 12. doi:10.1186/s12970-016-0137-8
Keywords: Cytokines; Triglycerides; High Fat Meal; Lipoprotein-Lipase Activity; Factor-Kappa-B; Physical-Activity